Tinjauan Hukum Pembangunan Berkelanjutan Proyek IKN dalam Mempertahankan Keseimbangan Ekosistem Lingkungan - Retno mulyaningrum (Perspektif Hukum, 2023)
The process of building the National Capital of the Archipelago/Nusantara (IKN) in East Kalimantan is currently underway. Criticism was received from various groups before and after several state agendas were carried out. However, as a consideration, it is better to carry out periodic reviews from a legal, social and environmental perspective in order to get more attention in managing the environment of the new capital city. The theory of sustainable development and public policy theory becomes a balance when there are deviations and even environmental damage that can harm living things. The legal certainty that has been contained in several regulations such as the PPLH Law, the State Policy Law Regional Regulations of the Province of East Kalimantan which address the environment is used in analysis related to the development of the IKN aims to find out the balance and good steps to be taken going forward with the IKN development process.